2017
DOI: 10.18632/oncotarget.14924
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-derived ETS factor improves prognosis and represses proliferation and invasion in hepatocellular carcinoma

Abstract: Prostate-derived E-twenty-six (ETS) factor (PDEF), an epithelium-specific ETS transcription factor, regulates carcinogenesis and tumor progression. The prognostic importance and biologic functions in hepatocellular carcinoma (HCC) have not been established. We investigated PDEF expression in 400 HCC patients using quantitative real-time polymerase chain reaction, western blot and immunohistochemistry analysis. PDEF expression was significantly lower in tumors than in peritumoral tissues. Lower PDEF levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…These patients were post-surgically monitored until July 7, 2015, with a median follow-up of 54 months (range: 1-66 months). The follow-up procedures were performed as described in our previous reports 17. The patients did not exhibit signs of distant metastasis.…”
Section: Methodsmentioning
confidence: 99%
“…These patients were post-surgically monitored until July 7, 2015, with a median follow-up of 54 months (range: 1-66 months). The follow-up procedures were performed as described in our previous reports 17. The patients did not exhibit signs of distant metastasis.…”
Section: Methodsmentioning
confidence: 99%
“…SPDEF mRNA and protein expression is reduced in HCC, particularly in poorly differentiated tumours, and is associated with worse patient outcome [ 98 ]. Knockdown of SPDEF in HCC cell lines increased cell proliferation, survival and invasion in vitro and tumour growth and metastasis in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The increased invasion and metastasis are likely due to increased expression of the EMT driver, SLUG. Comparatively, overexpression of SPDEF in HCC cell lines decreased proliferation and increased apoptosis [ 98 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on BC have shown that PDEF promotes the luminal differentiation of basal mammary epithelial cells and contributes to endocrine resistance in ER-positive BC [ 13 ]. In contrast, other studies have shown that PDEF levels decrease in highly malignant, ER-negative and basal-like BC cells and that re-expression of PDEF in these cells reduces their migration and invasion, suggesting that PDEF functions as a tumour suppressor [ 33 , 34 ]. It is difficult to assess the relevance of ectopic PDEF expression in tumour cell lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing PDEF function in different cancers suggest its important role in tumorigenesis [ 32 , 33 ]. Studies on BC have shown that PDEF promotes the luminal differentiation of basal mammary epithelial cells and contributes to endocrine resistance in ER-positive BC [ 13 ].…”
Section: Discussionmentioning
confidence: 99%